Reliability and validity of a novel trunk-strength assessment for high-performance sprint flat-water kayakers - Steeves, D.; Thornley, L. J.; Goreham, J. A.; Jordan, M. J.; Landry, S. C.; Fowles, J. R. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine the reliability and validity of a novel trunk maximal isometric force assessment involving 7 different tasks with 200-m times for elite sprint flat-water kayakers. Methods: Ten elite sprint flat-water kayakers performed a series of maximal isometric voluntary contractions (MVCs) on 2 separate days to assess reliability. MVC force was assessed as the participants sat on a modified kayak ergometer and applied their maximal isometric force to a uniaxial load cell during 7 different tasks. The 7 tasks of interest were a seated trunk-forward flexion, bilateral (left and right) rotational pulls, bilateral rotational pushes, and a sport-specific bilateral kayak-stroke simulation. Twenty elite flat-water kayak athletes (10 male and 10 female) participated in the validity portion by completing the series of tasks in conjunction with a 200-m race. Results: MVC force values ranged from 84 to 800 N across all participants and all tasks. The average coefficient of variation of the 7 tasks ranged from 2.4% to 7.7%. Regression analysis showed Pearson correlations ranging from -.84 to -.22 for both absolute and relative values with 200-m performance times. Conclusions: MVC force measured in each task was considered reliable as a small degree of variance between trials was found. The summation of the 7 trunk scores showed very strong correlations with on-water performance, indicating that this assessment is valid for elite sprint kayakers.